Fear-avoidance beliefs—a moderator of treatment efficacy in patients with low back pain: a systematic review - Wertli, Maria M.; Rasmussen-Barr, Eva; Held, Ulrike; Weiser, Sherri; Bachmann, Lucas M.; Brunner, Florian (The spine journal, 2014)
Psychological factors are believed to influence the development of chronic low back pain. To date, it is not known how fear-avoidance beliefs (FABs) influence the treatment efficacy in low back pain. To summarize the evidence examining the influence of FABs measured with the Fear-Avoidance Belief Questionnaire or the Tampa Scale of Kinesiophobia on treatment outcomes in patients with low back pain. This is a systematic review. Patients with low back pain. Work-related outcomes and perceived measures including return to work, pain, and disability. In January 2013, the following databases were searched: BIOSIS, CINAHL, Cochrane Library, Embase, OTSeeker, PeDRO, PsycInfo, PubMed/Medline, Scopus, and Web of Science. A hand search of the six most often retrieved journals and a bibliography search completed the search. Study eligibility criteria, participants, and interventions: research studies that included patients with low back pain who participated in randomized controlled trials (RCTs) investigating nonoperative treatment efficacy. Out of 646 records, 78 articles were assessed in full text and 17 RCTs were included. Study quality was high in five studies and moderate in 12 studies. In patients with low back pain of up to 6 months duration, high FABs were associated with more pain and/or disability (4 RCTs) and less return to work (3 RCTs) (GRADE high-quality evidence, 831 patients vs. 322 in nonpredictive studies). A decrease in FAB values during treatment was associated with less pain and disability at follow-up (GRADE moderate evidence, 2 RCTs with moderate quality, 242 patients). Interventions that addressed FABs were more effective than control groups based on biomedical concepts (GRADE moderate evidence, 1,051 vs. 227 patients in studies without moderating effects). In chronic patients with LBP, the findings were less consistent. Two studies found baseline FABs to be associated with more pain and disability and less return to work (339 patients), whereas 3 others (832 patients) found none (GRADE low evidence). Heterogeneity of the studies impeded a pooling of the results. Evidence suggests that FABs are associated with poor treatment outcome in patients with LBP of less than 6 months, and thus early treatment, including interventions to reduce FABs, may avoid delayed recovery and chronicity. Patients with high FABs are more likely to improve when FABs are addressed in treatments than when these beliefs are ignored, and treatment strategies should be modified if FABs are present.